Describing Occupational Therapy Practice for Evaluating Older Adults with Cognitive Impairments. (3rd April 2023) - Briskie-Semeniuk, Patricia; Bier, Nathalie; Couture, Mélanie; Vachon, Brigitte; Belchior, Patricia
Abstract: Aims: This study aimed to describe how occupational therapists evaluate older adults with cognitive impairments. Methods: A descriptive qualitative study design was used. Four focus groups were conducted with 16 occupational therapists working with cognitively impaired older adults in institutional and community care settings. An inductive thematic analysis of the content of the interviews was applied. Results: Occupational therapists described a three-stage assessment process that was predominantly occupation-based, linear and iterative: (a) gathering information from the older adult, their care network and family members to plan the assessment, (b) assessing cognitive impairment and occupational performance using non-standardized observations and standardized tests, and (c) applying clinical reasoning to predict further performance issues and safety. Despite using a predominantly occupation-based assessment process, occupational therapists reported a lack confidence to predict safety. Conclusion: Occupational therapists may require additional knowledge, skills and tools to support them in assessing older adults with cognitive impairments.